PENGARUH MACAM VARIETAS DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays.) - Moh. Ruin Moh. Ruin; Teguh Supriyadi Teguh Supriyadi; Tyas Soemarah KD Tyas Soemarah KD Tyas Soemarah KD (JURNAL ILMIAH AGRINECA, 2010)
The research aim to know influence of corn variety and dosage of NPK fertilizer on  corn. Research was conducted since February until Juny 2008 in Kedokan Sayang Village, Sub District Tarub, District Tegal, Central Java, Altitude 25 meters from sea surface with soil type alluvials, in the Laboratory of Agriculture Faculty, Tunas Pembangunan University. Temperature 29 – 32 º C. Research used the factorial with based pattern RCBD (Randomized Completely Block Design) consist of 2 treatment factor with 3 times restating. Results of research indicates that : (1) Treatment Variety of Corn was very significant to number of  rows  per cob and significant to number of seed per cob, non significant to hight plant, weight  fresh of  plant, weight  dry of plant, weight dry of  minner per plant, weight dry of  minner per plot and weight dry of  minner per 100 seeds. (2) Dosage of NPK fertiliser was non significant to all parameter observation object. (3) Interaction between variety of corn and  dosage of NPK fertilizer was significant to hight plant. (4) Highest dry minner seeds weight 4,57 Kg/plot (9,777 ton/Ha) obtained by treatment of V1D1 this  is combination treatment  of Variety Corn P21 and dosage of NPK  fertilizer 200 Kg/Ha and lowest dry minner seeds weight  1,87 Kg/plot (3.32 ton/Ha) obtained at treatment of V2D2 this is combination of Variety Corn Bisi2 and dosage of NPK  fertilizer 400 Kg/Ha.